Message Gateway-Based Control System for Parents on the use of Motorcycle Vehicles in Young Adolescents - Wirawan, Nanda Tommy; Rahman, Sepsa Nur (Politeknik Ganesha Medan, 2019)
Given the large number of fatalities and the amount of economic and social losses caused by road accidents, it is necessary to build a road safety culture early on in Indonesia. Various programs and socialization efforts have been carried out to reduce the high number of accidents. One of the socialization steps is the concept of introducing SMS gateway surveillance for parents to be able to supervise the use of vehicles by young teenagers. The concept of notification in the form of an SMS gateway is more specifically devoted to motorbike riders for teenagers who are only able to drive on public roads, bearing in mind young teenagers are often reckless then it is the biggest contributor to accidents in Indonesia. This research is focused on the problem of means of use and supervision in driving, especially for parental supervision of young teenagers. Using this system will reduce road accidents, because young teenagers will be monitored by this system and notified their parents to take further action against vehicle users. This form of system works if the driver crosses the normal speed of driving, the system will automatically send sms to the parents of the children who are driving, the parents' supervision of the child in driving increases so that the level of traffic accidents will decrease, and parents can find out where their child is.